Conducting Market Research: An Aid to Organisational Decision Making - Nyukorong, Remy (European Scientific Journal, ESJ, 2017)
As firms grow more and more in global markets, the role of reliable, verifiable, timely and high quality marketing research information to support decision-making becomes increasingly indispensable. The effectiveness and usefulness of decision-making is directly connected to the broad condition of the preferred sector(s) of the global market. To obtain complete information regarding the market entails designing and completing a significant number of activities arranged in logical sequence. Marketing research is the principal means by which firms comprehend existing and potential customers. Thus, this conceptual paper proposes a framework for accomplishing global market research ventures. In addition, the paper outlines a number of factors that should be taken into consideration by scholars who engage in global market research ventures. The factors represent the diversity of challenges that should be focussed on in conducting research globally. Specific attention is given to the nuances linked to data collection and analysis. Taking cognisance of the above, the informational core in the management of global firms should be assessed according to its value and role in world-wide marketing management. Lastly, technological advances should be integrated into the market research process in order to ease and accelerate research performed across national borders.